Adoption of Open Source technology in Higher Education Sector in Malaysia - Navindran M, (2009)
The scope of this research is to analyze Malaysian higher education community view on the open source technology. The objectives of this paper are to identify the factors which contribute to the open source usage among the Malaysian higher education community and to build a model to measure the open source usage among the Malaysian higher education community.